O papel do programa de educação tributária na mudança de hábito da população jovem do Espírito Santo: o caso dos municípios de São Matheus e Muniz Freire - Lavor, Anthony Fermino Repetto (2003)
This paper intends to propose a study to evaluate and analyse the influence of tax education in the behavior of young inhabitants of the Espirito Santo State living in the cities of Muniz Freire and São Mateus. The context of the problem under investigation consists in the context of a frequent conflict between consumers, the state and companies. These conflicts arise because the state does not provide sufficient and adequate services that lie under its responsability. Due to this fact, companies often conclude that it is not worthwhile to pay state taxes, and the consumer has great trouble when trying to obtain the rights they are entitled to from the companies and from the state. Therefore, the intermediate aims of this paper were to research behavior related to the moment of purchase and the reception of a bill of sale, especifically, if mechanisms of pressure, involvement and personal commitment, exert any influence over the consumers request for a tax receipt. The methodology to reach these objectives was a field survey through questionnaires. The final results show that through the tax education the students are assimilating the importance of the taxes.